2018
DOI: 10.1177/0009922818787280
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Cardiology Evaluation for Innocent Heart Murmur: Echocardiogram Utilization

Abstract: We conducted a retrospective study to identify electrocardiogram (ECG) and echocardiogram utilization among patients presenting for a follow-up cardiology evaluation with innocent heart murmur between 2012 and 2014. The 2014 echocardiogram Appropriate Use Criteria was applied. We observed high rates of ordering ECGs and echocardiograms on follow-up visits (79% and 36%); only 1 patient had an appropriate indication for echocardiogram while the rest had rarely appropriate indication. Having had an ECG done did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…in the year 2014 which clearly notes transthoracic echocardiogram for presumed innocent heart murmur as “rarely appropriate” indication [18]. Despite published guidelines, there is a significant utilization of transthoracic echocardiography as well as recurrent cardiology visits for innocent heart murmur [13-14]. Giuffre et al and Bardsen et al looked at parental anxiety after a diagnosis of childhood heart murmur [15,17].…”
Section: Reviewmentioning
confidence: 99%
“…in the year 2014 which clearly notes transthoracic echocardiogram for presumed innocent heart murmur as “rarely appropriate” indication [18]. Despite published guidelines, there is a significant utilization of transthoracic echocardiography as well as recurrent cardiology visits for innocent heart murmur [13-14]. Giuffre et al and Bardsen et al looked at parental anxiety after a diagnosis of childhood heart murmur [15,17].…”
Section: Reviewmentioning
confidence: 99%
“…In the SCAMPs ® chest pain cohort, an echocardiogram was obtained by a cardiologist in 23.4% of patients despite not meeting the medical red-flag criteria. 4 In children who presented for a second cardiology visit with innocent heart murmur, Dalal et al 25 demonstrated that echocardiograms were obtained in 36% of all follow-up visits. In all but one, the indication for the echocardiogram was deemed as rarely appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…The ACCU consists of 26 private and shared beds located within a free-standing quaternary Children’s Hospital in Washington, DC. 4 , 5 The ACCU is not a closed cardiac unit, though cardiology patients and cardiac surgery patients are solely admitted to the unit. Nephrology patients are preferentially admitted to the ACCU, and other services could be admitted during high census times when their traditional units are full.…”
Section: Methodsmentioning
confidence: 99%
“…A centerline shift was determined based on 8 or more datapoints above or below the centerline. 4 , 5 …”
Section: Methodsmentioning
confidence: 99%